Museum of Weapons as a History Learning Resource in Palu City - Abdullah, Amirah Mahmud; Najamuddin, Lukman; Haliadi, Haliadi; Latief, Juraid Abdul (Journal of Education Method and Learning Strategy, 2023)
The Museum of Weapons, located in the heart of Palu, is an important learning resource for the next generation, ensuring that the values of the cultural legacy bequeathed by the warrior heroes of Tanah Kaili are not forgotten. Learning the history of the Guma weapon used by Tanah Kaili soldiers at the Weapons Museum is necessary to instill pride in the younger generation in the heroes who have battled. Not forgetting their own region's past, but yet not being blind to it. The Museum of Weapons is expected to educate the future generation about the importance of preserving the cultural heritage of Guma weapons. This article uses a qualitative descriptive method. The data collection techniques used in this research are; observation, interviews, and documents. Then the data is processed by reducing data, presenting data, and verifying data/conclusion. The findings indicate that the Guma Museum is unique in that the historical sources that have formed collections of items (artifacts) are traditional weaponry. There are 42 different kinds of traditional weapons on display. This museum, which is used as a source of studying history, has proven to be helpful in raising the historical consciousness of students in Palu City. Learning about traditional weapons in Tanah Kaili through educational travel to the Weapons Museum inspired students to be proud, responsible, and obligated to protect and preserve cultural heritage objects left by Tanah Kaili's warrior ancestors. This is what raises pupils' historical awareness in Palu City.